Implementasi Program Teratai Sebagai Model Edukasi Berbasis Sekolah Untuk Peningkatan Kepatuhan Konsumsi Tablet Tambah Darah Pada Remaja Putri - Rahmadana, Muhammad Haritsyah; Monika, Cici; Amalia, Vella; Hidzra Wafi Habib; Siregar, Fatia Putri Barokah; Rima Semiarty; Hardisman, Hardisman (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Anemia among adolescent girls remains a major public health problem, largely due to poor adherence to iron supplementation programs. According to the 2024 Nanggalo Public Health Center report, SMP IT Dar El Iman Padang had the highest rate of anemia among adolescent girls in the area. This community engagement project aimed to improve knowledge and adherence to iron tablet (TTD) consumption through the TERATAI (Teratur Minum Tablet Tambah Darah, Tolak Anemia) program. The activity was conducted on August 25, 2025, at SMP IT Dar El Iman, Padang, involving 114 seventh-grade female students. Interventions included interactive health education, educational video screening, poster distribution, appointment of anemia ambassadors, and training on the use of Google Forms for monitoring TTD consumption. Evaluation was carried out through pre- and post-tests to assess knowledge improvement and through a four-week monitoring of adherence. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of p<0.05. The mean knowledge score increased from 65.4 ± 9.2 to 82.1 ± 8.5 after the intervention (p<0.001), representing an average improvement of 25.5%. TTD adherence rose from 58.7% to 86.4% by week four. Furthermore, 91% of participants reported that the activity was engaging and beneficial, and teachers observed greater student motivation to take TTD regularly. The TERATAI program effectively improved students’ knowledge and adherence to TTD consumption. This school-based educational approach, supported by healthcare professionals and teachers, demonstrated positive impacts and is highly replicable as a sustainable model for adolescent anemia prevention programs.